The role of plant proteases in the response of plants to abiotic stress factors - Luciński, Robert; Adamiec, Małgorzata (Frontiers in Plant Physiology, 2023)
The primary function of proteolytic enzymes is the hydrolysis of peptide bonds. Enzymes responsible for catalyzing this reaction are commonly referred to as proteases. The vast majority of these enzymes belong to the class of hydrolases and operate in aqueous environments.However, there is a distinct group of proteases known as intramembrane proteases, which are integral membrane proteins capable of cleaving peptide bonds in the hydrophobic environment of biological membranes. Proteolysis serves several essential functions in plant cells, ranging from the degradation of damaged and unnecessary proteins to the removal of non-functional protein aggregates. It plays a role in the quality control system for proteins and even releases transcription factors from membrane proteins. Proteolytic processes are indispensable at every stage of plant development and allow for the modification of the cell's protein composition based on developmental needs and environmental requirements. Proteases are also enzymatic components of the cell that facilitate the efficient regeneration of many key metabolic pathways, such as photosynthesis and respiration. The response of plant cells and the entire plant organism to various biotic and abiotic stresses often requires the remodeling of metabolic pathways, the regeneration of key enzymatic complexes, or changes in the protein profile. By participating in all these processes, proteases constitute a crucial element of the cellular response to environmental stresses. The aim of this work is to review the role that individual proteases play in the response of plant cells to abiotic stress factors, such as drought, salinity, cold, temperature, and light.